(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Purulent pericarditis is a rare but life-threatening bacterial infection. Most patients have preced ing or concurrent infection that is the source of pericarditis. These infections include pneumonia, meningitis, acute osteomyelitis, and acute soft tissue infections. In the present case bacterial cellulitis was the source of infection. Both the doctors and the patient contributed in act of negligence, which lead to the death the patient